2019
DOI: 10.1177/1049909119851470
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Motivational Interviewing to Enhance Advance Directive Completion in Latinos With Chronic Illness: A Randomized Controlled Trial

Abstract: Background: End-of-life (EOL) care for Latinos with chronic illness is a critically important problem. Latinos with chronic illness suffer worse health outcomes and poorer quality of care due to various issues occurring in care delivery systems. Latinos are less likely than non-Hispanic whites to prepare an advance directive (AD) for health-care decision-making that impacts treatment decisions for when EOL is near. Advance care planning (ACP) interventions tailored specifically for Latinos have rarely been imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…This cross-sectional study used baseline data collected from a pilot randomized clinical trial; and the methods for this study have been reported elsewhere. 25 This study received IRB approval from New Mexico State University review board. Participants were screened and provided written informed consent prior to participating in this study and were provided a $20 gift-card after they completed the study as a token of appreciation for sharing their perspectives and time.…”
Section: Methodsmentioning
confidence: 99%
“…This cross-sectional study used baseline data collected from a pilot randomized clinical trial; and the methods for this study have been reported elsewhere. 25 This study received IRB approval from New Mexico State University review board. Participants were screened and provided written informed consent prior to participating in this study and were provided a $20 gift-card after they completed the study as a token of appreciation for sharing their perspectives and time.…”
Section: Methodsmentioning
confidence: 99%
“…Documentation of ACP/AD: 54 RCTs evaluated documentation of ACP or AD 24 29–31 35 40–43 59 61 64 68 71 74 81 82 86 91 101 110–112 118–148. Of the 34 (63%) showing a positive and significant effect of the intervention on documentation, 20 were high-quality, 24 (71%) were communication interventions24 30 31 35 41 42 59 64 68 91 101 111 112 118–128 including 1 with a decision aid component,118 8 were decision aids only82 86 129–134 and 2 were AD-only interventions 43 135…”
Section: Resultsmentioning
confidence: 99%
“…Of the 16 studies retained (online supplemental table 1), the largest portion (11 studies) made use of an interview or conversation to address the topic of ACP. [28][29][30][31][32][33][34][35][36][37][38] Conversations were led by facilitators including (trained) nurses, 28 29 32 34-36 38 psychologists, 31 32 37 social workers [31][32][33] or graduate students. 31 32 Five conversation interventions also included the provision of conversation summaries and/or ADs completed during the conversation to the healthcare provider (general practitioner or treating physician) or placement of documentation in the patient's health record.…”
Section: Intervention Componentsmentioning
confidence: 99%
“…One study reported that, additionally, Latinos may not want to burden family members with distressing issues such as end-of-life conversations. 33 Attending to barriers such as those posed by language and health literacy can increase the likelihood of intervention success. 40 The authors of six studies reflected on the impact of the patient's illness experience on study outcomes.…”
Section: What Impacts Whether or Not The Intervention Achieves The Desired Outcome?mentioning
confidence: 99%